PAF-derived nitrogen-doped 3D Carbon Materials for Efficient Energy Conversion and Storage - Xiang, Zhonghua (Sci Rep, 2015)
Owing to the shortage of the traditional fossil fuels caused by fast consumption, it is an urgent task to develop the renewable and clean energy sources. Thus, advanced technologies for both energy conversion (e.g., solar cells and fuel cells) and storage (e.g., supercapacitors and batteries) are being studied extensively. In this work, we use porous aromatic framework (PAF) as precursor to produce nitrogen-doped 3D carbon materials, i.e., N-PAF-Carbon, by exposing NH(3) media. The “graphitic” and “pyridinic” N species, large surface area, and similar pore size as electrolyte ions endow the nitrogen-doped PAF-Carbon with outstanding electronic performance. Our results suggest the N-doping enhance not only the ORR electronic catalysis but also the supercapacitive performance. Actually, the N-PAF-Carbon obtains ~70 mV half-wave potential enhancement and 80% increase as to the limiting current after N doping. Moreover, the N-PAF-Carbon displays free from the CO and methanol crossover effect and better long-term durability compared with the commercial Pt/C benchmark. Moreover, N-PAF-Carbon also possesses large capacitance (385 F g(−1)) and excellent performance stability without any loss in capacitance after 9000 charge–discharge cycles. These results clearly suggest that PAF-derived N-doped carbon material is promising metal-free ORR catalyst for fuel cells and capacitor electrode materials.